Messen beruflicher Kompetenz - Rauner, Felix; Grollmann, Philipp; Martens, Thomas (2007)
Abstract: Felix Rauner, Philipp Grollmann und Thomas Martens present an approach to the measurement of professional competences, which is based on prior experiences and results from the evaluation of a pilot study on the re-design of vocational profiles within a German auto manufacturer.
Keywords: ⛔ No DOI found